Bacteriological profile of diabetic foot - Shah, Priti; Eswarawaka, Mridula; Anne, Dinesh; Reddy M., Sai Charan; Shah, Pranjal; Srivastava, Neha (International Surgery Journal, 2021)
Foot infections in patients with diabetes mellitus are a major cause of morbidity, can lead to gangrene and ultimately amputation of the limb. Aim of the study was to determine the type of microorganisms isolated from the Diabetic foot ulcer and antibiotic resistance pattern. We have included 50 patients having diabetic foot ulcers of Wagner's grade 1 or above in our study. Debrided tissue, pus, or swabs from the base of the ulcers were subjected to aerobic and anaerobic culture. The organisms were identified, and further antibiotic sensitivity was conducted. Seventy-two aerobic and 13 anaerobic organisms were isolated. Among the aerobic and anaerobic bacteria isolated, most predominant organisms were S. aureus and Bacteroides spp.; respectively. Of the S. aureus, 77.8% were methicillin resistant, while 42.1% of gram-negative Enterobacteriaceae were extended spectrum beta-lactamase (ESBL) positive. Klebsiella spp. was the highest ESBL producer. Acinetobacter spp. was the highest MBL producer. Most sensitive drugs for S. aureus were linezolid, vancomycin and amikacin. Gram-negative bacteria were mostly sensitive to piperacillin-tazobactam and amikacin. Pseudomonas spp. were usually sensitive to meropenem, piperacillin -tazobactam. Acinetobacter spp. was sensitive to colistin, tigecycline. As diabetic ulcers are often infected by multidrug-resistant bacteria, a knowledge of the common bacterial pathogens implicated as well as their sensitivity pattern helps the clinician to choose the proper antibiotic for a timely treatment.